Anti-angiogenic effect of nano-formulated water soluble kaempferol and combretastatin in an in vivo chick chorioallantoic membrane model and HUVEC cells - Gowtham Kumar Subbaraj (17807615) (2023)
The present study evaluated the efficacy of nano-formulated water-soluble kaempferol and combretastatin alone and combined against the native kaempferol and combretastatin on angiogenesis. The solvent evaporation method was used to synthesize the nano-formulated water-soluble kaempferol and combretastatin and characterized using various analyses such as dynamic light scattering (DLS) and Fourier-transform infrared (FT-IR) spectroscopy.The anti-angiogenic activity of native, nano-formulated water-soluble kaempferol and combretastatin was investigated by cell viability on HUVEC and A498 cell lines, while chick chorioallantoic membrane (CAM) assay was utilized to assess morphometric and histopathological changes, and mRNA expressions of VEGF-A and FGF2 using qRT-PCR. MTT assay results revealed that the combination of nano-formulated water-soluble kaempferol and combretastatin significantly reduced the cell viability compared to control, individual treatments of native, nano-formulated water-soluble kaempferol, and combretastatin. Morphometric analysis of CAM showed that treatment with nano-formulated water-soluble kaempferol and combretastatin caused a substantial decrease in density, vessel network, branch points, and nets of CAM blood vessels. The histopathological results of CAM showed the irregular shape of blood vessels at the thin stratum of chronic endoderm, and blood capillaries were diminished compared to the control. In addition, the mRNA expression levels of VEGF-A and FGF2 were significantly decreased compared with native forms. Therefore, the findings of this study indicate that nano-formulated water-soluble combretastatin and kaempferol suppress angiogenesis by preventing the activation of endothelial cells and suppressing factors of angiogenesis. Moreover, a combination of nano-formulated water-soluble kaempferol and combretastatin worked much better than individual treatments. Other Information Published in: Biomedicine & Pharmacotherapy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.biopha.2023.114820